Mapeamento de áreas utilizando o GPS de dispositivos móveis - Panho, Ricardo (2017)
With the advancement of technology, it has become very common the use of smartphone's GPS to perform people daily tasks. Tasks such as locate devices, mark important places, define routes through maps, among many other tasks that can be performed according to the functionalities of each application. The majority of the population has already had to perform a measurement of a terrain, but in some situations, it is necessary to hire a professional to measure the correct geographical coordinates, which has a high monetary cost. In this work was developed an application to measure land using geographic coordinates. The application was developed for smartphones with Android operating system, since these have a lower cost and are also easily accessible to users. For the development we use the Android Studio software, which allows to write the codes and use all available features on GPS, maps and other features of the device and operating system. As a result of this work, an application was obtained capable of performing measurements on land. In addition to functionality, the user is also able to record the measurements to storage the history of the terrains already measured.